The Effect of Local Tournament Incentives on Firms' Performance, Risk-Taking Decisions, and Financial Reporting Decisions - Ma, Matthew; Pan, Jing; Stubben, Stephen R. (The Accounting Review, 2020)
ABSTRACT This study documents the existence of local employment preferences for corporate executives and examines how the compensation of executives' local peers affects their own performance, risk-taking decisions, and financial reporting decisions. We find that external hires of new CEOs (CFOs) are five (eight) times more likely to be from local firms than non-local firms. We also find that local tournament incentives—as proxied by the pay gap between an executive and higher-paid executives in the area—are associated with stronger performance, greater risk taking, and more financial misreporting. We find consistent results using a difference-in-differences analysis that exploits plausibly exogenous variation in local tournament incentives caused by the sudden death of a local CEO. Our findings are consistent with executives taking actions to compete for a promotion to a nearby firm with higher pay.